Groenlandia densa (L.) Fourr. (Potamogetonaceae) — представник нового для флори України роду - Борсукевич, Л.М. (Український ботанічний журнал, 2010)
Новый для флоры Украины вид Groenlandia densa (L.) Fourr. обнаружен в пруду г. Борислав. Дано его морфологическое описание, проанализировано географическое распространение, представлена экологическая характеристика местообитания. Groenlandia densa (L.) Fourr. is reported for the first time for the Ukrainian flora. It was found in a pond in the town of Boryslav. Morphological description of the species is given. Data on the geographic range of the species and information on ecological characteristics of the new locality are also provided.